A review on utilization of different concretes as in-filled steel hollow column subjected to fire loading. (1st February 2021) - Zuhan, Nurizaty; Ab Kadir, Mariyana Aida; Mohamad Ali Mastor, Muhammad Najmi; Ngian, Shek Poi; Mohd. Sam, Abdul Rahman
Abstract : Purpose: Concrete-filled steel hollow (CFHS) column is an innovation to improve the performance of concrete or steel column. It is believed to have high compressive strength, good plasticity and is excellent for seismic and fire performance as compared to hollow steel column without a filler. Design/methodology/approach: Experimental and numerical investigation has been carried out to study the performance of CFHS having different concrete in-fill and shape of steel tube. Findings: In this paper, an extensive review of experiment performed on CFHS columns at elevated temperature is presented in different types of concrete as filling material. There are three different types of concrete filling used by the researchers, such as normal concrete (NC), reinforced concrete and pozzolanic-fly ash concrete (FC). A number of studies have conducted experimental investigation on the performance of NC casted using recycled aggregate at elevated temperature. The research gap and the recommendations are also proposed. This review will provide basic information on an innovation on steel column by application of in-filled materials. Research limitations/implications: Design guideline is not considered in this paper. Practical implications: Fire resistance is an important issue in the structural fire design. This can be a guideline to define the performance of the CFHS with different type of concrete filler at various exposures. Social implications: Utilization of waste fly ash reduces usage of conventional cement (ordinary Portland cement) in concrete production and enhances its performance at elevated temperature. The new innovation in CFHS columns with FC can reduce the cost of concrete production and at the same time mitigate the environmental issue caused by waste material by minimizing the disposal area. Originality/value: Review on the different types of concrete filler in the CFHS column. The research gap and the recommendations are also proposed.